The Effectiveness of Storytelling Method in Developing Children’s Receptive and Expressive Language Skills in Raudhatul Athfal Nurul Islam Batam City - Roselina, Roselina (Jurnal Indonesia Sosial Sains, 2024)
This research aims to analyze the application of the game of arranging number blocks in developing children's fine motor skills in RA Nurul Islam, Simpang Sungai Duren Village, Jambi Luar Kota District, Muaro Jambi Regency. The research method uses a descriptive qualitative approach. Data collection was carried out by observation, interviews and documentation. Data analysis uses data reduction, data presentation, data verification and conclusion. The results of this research are (1) The learning process through the activity of arranging number blocks has been carried out effectively. The development of children's fine motor skills implemented through the game of arranging number blocks and delivered by educators has achieved the desired results. Children can arrange the number blocks in an orderly layout, sequence the numbers correctly, differentiate between various colours, arrange the numbers from 1 to 20 properly, and can arrange the blocks vertically. (2) Obstacles that arise during the application of playing with number blocks in developing fine motor skills in group B children at RA Nurul Islam can come from internal factors, such as the child's level of interest, mood and level of willingness to learn. (3) Efforts to develop children's fine motor skills at RA Nurul Islam through playing with number blocks, this approach makes it possible to form several groups of children. Children are invited to participate in various activities, such as competitions in arranging numbers from 1 to 20 or working together to complete tasks given by the teacher.